Pruned Multiangle Resolution Fast Beamforming. (4th June 2008) - Yoon Yoon, Yeo-Sun Yeo-Sun; Kaplan Kaplan, Lance M. Lance M.; Oh Oh, Seung-Mok Seung-Mok; McClellan McClellan, James H. James H.
Abstract : Delay-and-sum (DS) beamforming is a simple processing method that can estimate the direction-of-arrival from multiple signal sources. The major advantage of DS beamforming is that it can handle wideband as well as narrowband signals. However, DS beamforming exhibits high computational complexity. The multiangle resolution fast beamformer was proposed as a computationally efficient approximation of DS beamforming, reducing the computational order of complexity fromO ( n 3 ) toO ( n 2 log   n ) . In this paper, we introduce the pruned multiangle resolution fast beamformer to further reduce the computational complexity. The new algorithm includes an energy detector at intermediate stages of the fast beamformer to prune sectors that do not exhibit increasing energy consistent with coherent integration. Simulations are provided to assess the performance of the pruned fast beamformer. One use for the estimates from the pruned fast beamformer is to initialize high-resolution direction-of-arrival (DOA) estimators such as coherent signal subspace methods.